M101, a therapeutic oxygen carrier derived from Arenicola marina, decreased Porphyromonas gingivalis‐induced hypoxia and improved periodontal healing. Issue 11 (13th June 2022) - Batool, Fareeha; Petit, Catherine; Stutz, Céline; Özçelik, Hayriye; Gegout, Pierre‐Yves; Benkirane‐Jessel, Nadia; Delpy, Eric; Zal, Franck; Leize‐Zal, Elisabeth; Huck, Olivier
Abstract: Background: Porphyromonas gingivalis exacerbates tissue hypoxia and worsens periodontal inflammation. This study investigated the effect of a therapeutic oxygen carrier (M101), derived from Arenicola marina, on hypoxia and associated inflammation in the context of periodontitis. Methods: The effect of M101 on GLUT‐1, GLUT‐3, HIF‐1α, and MMP‐9 expression, hypoxia, and antioxidant status in oral epithelial cells (EC) exposed to CoCl2 (1000 μM), P. gingivalis (MOI 100), and CoCl2 + P. gingivalis was evaluated through hypoxia detection fluorescence assay, antioxidant concentration colorimetric assay, and RTqPCR. Evaluation of M101 on EC proliferation was evaluated in an in vitro wound assay. In experimental periodontitis, periodontal wound healing and osteoclastic activity were compared among natural wound healing, placebo, and gels containing M101 (1 and 2 g/L) groups through histomorphometry and TRAP (tartrate‐resistant acid phosphatase activity assay) assay respectively. The expression of HIF‐1α, MMP‐9, and NFκB in periodontal tissues was also evaluated through immunofluorescence studies. Results: M101 downregulated GLUT‐1, GLUT‐3, HIF‐1α, and MMP‐9 levels in EC exposed to CoCl2, P. gingivalis, and CoCl2 + P. gingivalis ( p < 0.05). Fluorescence and colorimetric analyses confirmed hypoxia reduction and antioxidant capacity improvement in such EC upon M101 treatment. Moreover, M101 improved significantly the in vitro wound closure. In vivo, the attachment level was significantly improved, and osteoclastic activity was reduced in mice treated with M101 gels compared to placebo and natural wound healing groups ( p < 0.05). HIF‐1α, MMP‐9, and NFκB expression in periodontal tissues was reduced in M101 gels treated mice compared to the controls. Conclusion: M101 showed promise in resolving hypoxia and associated inflammation‐mediated tissue degradation. Its potential in the clinical management of periodontitis must be further investigated.